Selinexor for advanced hematologic malignancies. Issue 10 (23rd August 2020) - Walker, Janek S.; Garzon, Ramiro; Lapalombella, Rosa
Abstract: Recent measures to classify novel molecular targets with therapeutic potential across multiple hematologic tumors have identified the eukaryotic nuclear exporter, exportin 1 (XPO1), as a promising candidate. Molecular agents termed 'Selective Inhibitors of Nuclear Export' (SINEs) have been developed to selectively inhibit the essential regulatory functions of XPO1 in the eukaryotic cell and have been extensively studied in pre-clinical and clinical tumor models. Recently, selinexor (XPOVIO™), a first-in-class oral SINE molecule, was granted accelerated approval by the United States FDA for penta-refractory multiple myeloma. To establish a complete profile of this emerging drug candidate, this article reviews evidence collected from recent clinical studies against both solid and liquid tumors, describing selinexor as a promising new anti-cancer pharmaceutic against late-stage and highly aggressive tumors. With management of well-defined and predictable adverse effects, selinexor can be a life-saving therapeutic option in cancer patients with few alternatives.